FALSAFAH HUMA BETANG DI KALIMANTAN TENGAH: SEBUAH PERGULATAN IDENTITAS KONSELOR DAYAK MUSLIM - Riswanto, Dody (Institut Agama Islam Negeri Bengkulu, 2019)
The background of this research begins with the existence of Muslim Dayakcounselors in schools who get a negative perception of the social environmentregarding the existence of tribal counselors based on the religion adopted. Thisresearch method uses a qualitative approach where researchers act as keyinstruments, data collection techniques using interviews, observation,documentation studies and data triangulation, data analysis results from acombination of all data collection techniques that produce qualitative meaningsand propositions. The negative perception of the social environment is the mainproblem of the formation of the identity of Muslim Dayak counselors that isstrongly believed by the counselor, for which Muslim Dayak counselors needgood communication skills in conveying their identities to the socialenvironment so that the formation of self-identity can be done well. OverallMuslim Dayak counselors are able to introduce self-identity well without anyobstacles based on the religion adopted. This happened partly because of thephilosophy of Huma Betang which contained values of tolerance and mutualrespect among religious believers who could reduce negative perceptions of thesocial environment about the existence of Muslim Dayak counselors.